2006
DOI: 10.1002/erv.731
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of written emotional expression and planning with respect to bulimic symptoms and associated psychopathology

Abstract: Written emotional expression using Pennebaker's paradigm has been shown to produce significant improvements in health and psychological functioning in student groups and some clinical groups. This paradigm has not been examined with respect to disordered eating or its associated psychopathology. The current study examined 98 female university students (mean age ¼ 22.75 years, SD ¼ 8.31) who were randomly assigned to either an emotional expression writing condition relating to past trauma, or a control writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
5
23
1
Order By: Relevance
“…This is consistent with previous studies suggesting that emotionally-avoidant individuals are less likely to benefit from Pennebakerstyle writing tasks (Frayne & Wade, 2006;Stanton et al, 2002). The present findings furthermore suggest that individuals with avoidant traits may be reluctant to even engage in such writing tasks.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies suggesting that emotionally-avoidant individuals are less likely to benefit from Pennebakerstyle writing tasks (Frayne & Wade, 2006;Stanton et al, 2002). The present findings furthermore suggest that individuals with avoidant traits may be reluctant to even engage in such writing tasks.…”
Section: Resultssupporting
confidence: 93%
“…To date, there are also a small number of research studies suggesting that structured writing tasks can have a beneficial impact on various aspects of eating disorder symtomatology, including negative body image (Earnhardt, Martz, Ballard, & Curtin, 2002), bulimic symptoms (Frayne & Wade, 2006), thin-ideal internalisation (Stice, Shaw, Burton, & Wade, 2006), and eating disorder diagnosis (Robinson & Sefarty, 2008). The theoretical considerations outlined above suggest that expressive writing may particularly influence the cognitive, affective and interpersonal features associated with disordered eating, and a treatment programme which explicitly incorporates Pennebaker-style writing tasks has recently been developed (The Maudsley Eating Disorders Team, unpublished manual).…”
mentioning
confidence: 99%
“…Similar to findings of Frayne and Wade 18 and Earnhardt et al, 20 and in contrast to the findings of most therapeutic writing studies, the control task led to reductions in eating disorder symptomatology which were equivalent to those produced by the therapeutic writing task. This finding may have been influenced by a variety of factors.…”
Section: Equivalence Of Control Writing Tasksupporting
confidence: 85%
“…Symptom decreases were statistically but not clinically significant. 41 Although the present results are more favorable than those of most previous studies exploring the use of therapeutic writing in BN, 12,15,18 the small to moderate effect sizes, large number of nonimprovers, and equivalence to the control task, suggest that therapeutic writing tasks are of limited benefit to individuals experiencing symptoms of bulimia nervosa.…”
Section: Effects Of a Tailored Therapeutic Writing Task For Symptoms contrasting
confidence: 64%
“…Results of some studies have suggested disclosure can modestly reduce cognitive and interpersonal features associated with eating disorders. 37,38 Another group suggests that emotional arousal from disclosure may be less beneficial for this population. 11 Another possible moderating factor of emotional disclosure is the coping style of participants.…”
Section: Original Research and Contributionsmentioning
confidence: 99%